¿Qué cambios genera en la salud del suelo cuando pastoreamos los cultivos de cobertura? - Frasier, Ileana; Restovich, Silvina Beatriz; Scheneiter, Jorge Omar; Mattera, Juan; Pacente, Ezequiel Martin; Rorig, Marcela Laura; Etchegoyhen, S.; Giannini, Ana Paula (AAPRESID, 2024)
Poster